Mediating Role of Teaching Self-Efficacy in the Relationship Between Teaching Autonomy and Teacher Job Satisfaction - Hisashi A. Ikeda; Warren I. Mendoza; Ryan C. Villanueva; Francis Michael P. Yambao (Universal Journal of Educational Research, 2025)
Drawing on the Self-Determination Theory and the Social Cognitive Theory, this study examined the mediating effect of self-efficacy between teaching autonomy and job satisfaction in a Philippine aviation college. Data was collected through a census survey of 78 aviation instructors. Hayes’ PROCESS macro was utilized to test the mediation between the two variables; post-hoc power was 0.956. The study found that autonomy influenced self-efficacy (β=0.43, p=0.001) and job satisfaction (β=0.32, p=0.002). Self-efficacy also influenced satisfaction (β=0.43, p=0.001). The indirect effect accounts for 35% of autonomy’s total effect on job satisfaction which indicates partial mediation. The results suggest that providing instructors with an autonomy-supportive environment fosters better confidence in their teaching ability, which positively influences job satisfaction.